The South African genus Lepthercus Purcell, 1902 (Araneae: Mygalomorphae): phylogeny and taxonomy - Ríos-Tamayo, Duniesky; Lyle, Robin (Zootaxa, 2020)
After more than a century, the genus Lepthercus Purcell, 1902 is revised. Lepthercus dregei Purcell, 1902 and L. rattrayi Hewitt, 1917 are redescribed; with the female of L. dregei described for the first time. Nine new species of Lepthercus are described. A phylogenetic analysis with morphological characters using implied weights and parsimony as optimality criteria, suggests the separation of the genus in two clades. The first clade is formed by L. dippenaarae sp. nov., L. engelbrechti sp. nov., L. haddadi sp. nov., L. rattrayi Hewitt, 1917 and L. sofiae sp. nov., here denominated “Group haddadi”. The species L. confusus sp. nov., Lepthercus dregei Purcell, 1902, Lepthercus filmeri sp. nov., Lepthercus kwazuluensis sp. nov., Lepthercus lawrencei sp. nov. and Lepthercus mandelai sp. nov., form the second clade, here denominated “Group dregei”. The “Group haddadi” is characterized by males with a curved metatarsus I, and a swollen tibia I. The “Group dregei” is supported by the presence of small maxillary cuspules in males. A new diagnosis is provided for Lepthercus as well as an identification key for all species of the genus. New distribution maps for the genus in the country are also presented.